Progress in Artificial Economics Computational and Agent-Based Models - Li Calzi, Marco; Milone, Lucia; Pellizzari, Paolo; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2010)
Artificial economics aims to provide a generative approach to understanding problems in economics and social sciences. It is based on the consistent use of agent-based models and computational techniques. It encompasses a rich variety of techniques that generalize numerical analysis, mathematical programming, and micro-simulations. The peer-reviewed contributions in this volume address applications of artificial economics to markets and trading, auctions, networks, management, industry sectors, macroeconomics, and demographics and culture.
Markets and Trading -- Agent$1 (Bs Minimal Intelligence Calibration for Realistic Market Dynamics -- Trading on Marginal Information -- Stylized Facts Study through a Multi-Agent Based Simulation of an Artificial Stock Market -- Auctions -- A Variable Bid Increment Algorithm for Reverse English Auction -- Co-evolutionary Agents in Combinatorial Sealed-bid Auctions for Spectrum Licenses Markets -- The Effect of Transaction Costs on Artificial Continuous Double Auction Markets -- Networks -- The Rise and Fall of Trust Networks -- Simulations on Correlated Behavior and Social Learning -- Technology Shocks and Trade in a Network -- Management -- The (Beneficial) Role of Informational Imperfections in Enhancing Organisational Performance -- Social Interactions and Innovation: Simulation Based on an Agent-Based Modular Economy -- Threshold Rule and Scaling Behavior in a Multi-Agent Supply Chain -- Industry Sectors -- Information and Search on the Housing Market: An Agent-Based Model -- Adaptation of Investments in the Pharmaceutical Industry -- An Agent-Based Information Management Model of the Chinese Pig Sector -- Macroeconomics -- Wealth Distribution Evolution in an Agent-Based Computational Economy -- Endogenous Credit Dynamics as Source of Business Cycles in the EURACE Model -- Reinforcement Learning of Heterogeneous Private Agents in a Macroeconomic Policy Game -- Demographics and Culture -- Towards an Agent-Based Model of the Economic Development Process: The Dynamics of the Fertility Rate -- An Agent-Supported Simulation of Labour and Financial Markets for Migration Processes -- Sensitivity Analysis of an Agent-Based Model of Culture$1 (Bs Consequences for Trade.s
Keywords: Economics; Economics, Mathematical; Economics/Management Science; Game Theory/Mathematical Methods